PHENOMENOLOGICAL PERSPECTIVES ON SPACE IN THE READING OF DRAMA: AN ANALYSIS OF THERESE RAQUIN, VOR SONNENAUFGANG, AND THE THREE SISTERS - Kir, De Antoinette (My University, 1980)
In the Introduction chapter, the thesis outlines a basic premise concerning the reader of drama. This premise is then applied to three dramatic texts: Therese Raquin, Vor Sonnenaufgang, and The Three Sisters. The Introduction uses some of the writings of Roman Ingarden and Wolfgang Iser as a basis, although it does not rely on them exclusively. Following Ingarden, the thesis posits that the entities of author, text, and reader are necessary (but not exclusive) components in the existence of the literary work of art and states that it will concern itself specifically with the entities of text and reader. Within the text/reader relationship, it focuses on the reader's apprehension of the dramatic literary text as regards space. The thesis does not concern itself with the ontological status of the literary, work as such, but works from the premise, as elaborated by Ingarden and, subsequently, by Iser, that the literary text needs a reader in order to fulfill (at least some of) its potentialities as a text. It also posits that the process of reading is already partially prepared for within the text itself, i.e., that the text presumes future de-coding of itself by a reader and makes room for his collaboration towards the generation of a certain amount of meaning. The reader's most helpful tool in this participation process is the text's essential indeterminacy. During the linear process of reading, the reader is forced by the text's indeterminacy to fill gaps, make connections between the sometimes scattered schematized views, anticipate what is to come, or think back on what has already been read. Each text "intends" by its very "availability"; that is, because it has a certain number of pages upon which are arranged, in a chosen order, a set number of entities which allow for interpretation and manipulation by the imagination of the reader. No teleology or specific generation of meaning is intended by the thesis, however, when it says that the reader co-operates with the text in order to bring to fruition (some of) its "intention". Some of the specific problems which are inherent in treating the topic of the reading of drama are also discussed in the Introduction. The thesis maintains that, despite the traditional dichotomy that exists between text and performance, or drama and theatre, there is as much legitimacy in exploring the relationship between the reader and the dramatic literary text as there is in exploring the relationship between the reader and any other literary work of art. Since the dramatic text always always implies the visual and aural, however, it must always be read with performance in mind, and it thus sets up its own convention(s). The subsequent analysis of the three dramatic texts is done by focusing solely on the topic of [unclear word] of space. The choice of texts is relatively arbitrary in that it is not meant to proclaim what has been called the period of "naturalism" as the only or the best period to explore. The results of the analyses vary with the complexity of the texts chosen. However, the thesis concludes that the application of the theoretical stands outlined in the Introduction is just as legitimate for the dramatic literary text, within its own conventions, as it is for any other literary work.
Keywords: Comparative Literature; Comparative Literature